2022
DOI: 10.1021/acscatal.2c03772
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into (Tere)phthalate-Ester Hydrolysis by a Carboxylesterase and Its Role in Promoting PET Depolymerization

Abstract: TfCa, a promiscuous carboxylesterase from Thermobifida fusca, was found to hydrolyze polyethylene terephthalate (PET) degradation intermediates such as bis(2-hydroxyethyl) terephthalate (BHET) and mono-(2-hydroxyethyl)-terephthalate (MHET). In this study, we elucidated the structures of TfCa in its apo form, as well as in complex with a PET monomer analogue and with BHET. The structure–function relationship of TfCa was investigated by comparing its hydrolytic activity on various ortho- and para-phthalate ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Together with the previously obtained BHET and MHET degradation activities, and the fact that PET46 is a FAE, we assume hydrolysis happens at the polymer chain end (exo-activity), where 3PET is quickly cleaved to MHET units, which are subsequently converted to TPA and ethylene glycol (EG). This method of action has been proposed and experimentally shown recently for another 3PET-degrading esterase 45 , although their structures differ substantially (Supplementary Fig. S5d).…”
Section: Pet46 Is a Promiscuous Feruloyl Esterase That Hydrolyzes Mhe...mentioning
confidence: 77%
See 1 more Smart Citation
“…Together with the previously obtained BHET and MHET degradation activities, and the fact that PET46 is a FAE, we assume hydrolysis happens at the polymer chain end (exo-activity), where 3PET is quickly cleaved to MHET units, which are subsequently converted to TPA and ethylene glycol (EG). This method of action has been proposed and experimentally shown recently for another 3PET-degrading esterase 45 , although their structures differ substantially (Supplementary Fig. S5d).…”
Section: Pet46 Is a Promiscuous Feruloyl Esterase That Hydrolyzes Mhe...mentioning
confidence: 77%
“…Furthermore, PET46 was faster in degradation of the intermediates BHET and MHET. This makes PET46 a good candidate for evolution experiments towards a possible industrial application 45,69 .…”
Section: Discussionmentioning
confidence: 99%
“…They also investigate the catalytic activity of TfCa to DEP (Fig. 1 ), and found that TfCa completely converted DEP to MEP, but cannot further hydrolyze MEP to PA 24 , highlighting the significance of developing PAE hydrolases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, enzymatic depolymerization of plastics has emerged as an alternative technology to conventional mechanical and chemical plastic recycling approaches. Huge success has been achieved on the charicaterization and mechanistic study of several enzymes that depolymerize polyethylene terephthalate (PET) [21][22][23][24] . However, in addition to the production of monomers that form the plastics, PAEs are also released during the polymer hydrolysis process as they are not covalently bound in the plastics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation